The current state and characteristics of social responsibility of business - Tkachenko, N. A.; Chervonenko, N. M.; Knysh, E. G. (Zaporozhye Medical Journal, 2013)
The article analyzes the scientific approaches to the understanding of the social responsibility of business, its types and levels, display in pharmacy based on international experience.